Analysis integrated morphometric and occupation in small drainage basin: Case study of the Santa Maria stream, Conceição de Ipanema-MG (Research, Society and Development, 2020)
The integrated analysis of drainage basin, is an important and indispensable method of characterizing the hydrological behavior of a given territory. Those analyses with emphasis on morphometric parameters and data collected from the assessment of land use and occupation supports management and decision-making focused on the conservation of these environments. In this sense, the work aimed to characterize the drainage basin of Santa Maria stream, Conceição de Ipanema, MG. The study addresses the implementation of techniques for morphometric analysis with a view to determining the physical characteristics of the basin using Geographic Information Systems (GIS). The methodology relied on the use of Satellite Images, Topographic Charts, ArcGis Software and the performance of varied calculations of morphometric indices. The results showed that the study universe is a 4th order basin, with a tendency to a more elongated shape, medium drainage capacity, expressive permeability and low level of flood prone. The characteristics of land use and cover show that 65.23% of its extension refers to pasture areas, 33.25% correspond to native vegetation and only 1.52% are places that present their exposed soil. Consequently, there is a urgent need to act on vegetation restoration in riparian zones in order to maintain the quality and quantity of water in the region, as well as the preservation of native species and the proper management of land use and occupation.